Exploring the Happiness and Life Experiences of Nepalese People Living in the USA - Aryal, Pitambar; Karki, Tej Bahadur (Nepal Journal of Multidisciplinary Research, 2026)
Background: Nepal has been experiencing the rising academic and labor migration, and major labor migration to Europe, North America, Canada, and other countries in Asia, and seasonal migration to the Gulf and other nations of Asia. Whereas migrants to the Gulf and Asian destinations are notorious to go back to their home countries after the expiry of the contract, the migrants to Europe, North America, and Australia will tend to seek paths of legal settlement or permanent residence. This paper discusses some of the main questions associated with the experiences of Nepalese migrants in the United States: how happy they are, why they decide to stay longer, and how they communicate with their families in Nepal. Methods: The research design followed a mixed research design guided by the constructivist worldview. The Oxford Happiness Questionnaire (29 items, six-point Likert scale) was used to collect the data because it was supplemented with 14 demographic and socioeconomic statements (five-point Likert scale) and six open-ended questions focused on adjustments. The respondents were surveyed in both face-to-face and virtual formats and included 31 respondents representing various states such as Texas, Maryland, Pennsylvania, New York, and California and with different visa statuses. Results: These results indicate that the mean Nepalese migrant in the US claims that they are usually happy; they believe that there are job opportunities available, they find working hours to be manageable and they communicate with their family members in Nepal on a regular basis. But they are also sad because of physical separation with their families and a significant part of their income is spent on living. In general, the quality of life, educational level, employment, and income greatly determine the level of happiness. Novelty: Happiness is strongly influenced by quality of life, educational attainment, employment opportunities, social and cultural adjustment.